2013
DOI: 10.1177/0269094213496974
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced broadband access as a solution to the social and economic problems of the rural digital divide

Abstract: This article discusses the danger of a growing digital divide between rural and other areas. It presents broadband as increasingly necessary for the delivery of information, health, education, business, social security, public and leisure services. Access to broadband has become vital for rural communities to participate in a progressively digital economy and to overcome problems of physical and social isolation. Yet rural areas are among those most excluded from fast broadband developments. Although this is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
211
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(226 citation statements)
references
References 23 publications
3
211
0
12
Order By: Relevance
“…There are still segments of the population that are excluded on the basis of socio-economic disadvantage, age, and geography. This was illustrated by the fact that seven of our ten focus groups were held in urbanised areas, rather than rural areas which traditionally face issues of digital exclusion (Townsend et al, 2013). Accordingly, we used offline mechanisms of sampling to complement the online components, using a conventional snowball sampling technique for recruitment.…”
Section: Recruitment Strategiesmentioning
confidence: 99%
“…There are still segments of the population that are excluded on the basis of socio-economic disadvantage, age, and geography. This was illustrated by the fact that seven of our ten focus groups were held in urbanised areas, rather than rural areas which traditionally face issues of digital exclusion (Townsend et al, 2013). Accordingly, we used offline mechanisms of sampling to complement the online components, using a conventional snowball sampling technique for recruitment.…”
Section: Recruitment Strategiesmentioning
confidence: 99%
“…Handley et al conducted a survey of 1246 patients in rural Australia in 2014 to determine the feasibility of mental health treatments delivered online using two feasibility criteria: (1) internet access and (2) willingness to use internet services. This Australian study found that only 7% of those who would consider using an internet service cited lack of internet access as a barrier [10] but that rates of internet access decreased significantly with increasing rurality, which is also true in Scotland [11] .…”
Section: Socioeconomic and Geographic Factorsmentioning
confidence: 91%
“…They often demonstrate strong social capital and creativity (Falk & Kilpatrick 2000), but many face problems of isolation, accessibilities, depopulation and social cohesion (Townsend et al 2013). Such problems have often been referred to as the 'rural penalty' (Blanks Hindman 2000), and it is recognised that digital technologies and, in particular, broadband have much to offer in reducing this penalty.…”
Section: The Urban-rural Digital Dividementioning
confidence: 99%
“…Many of those interviewed had low levels of skill and confidence, characteristic of rural areas (Townsend et al 2013). A number of high bandwidth broadband requirements for business or personal/lifestyle purposes were identified by interviewees, despite the fact that they were largely unable to use them.…”
Section: The Role Of Broadband In Remote Rural Placesmentioning
confidence: 99%
See 1 more Smart Citation